The Effectiveness of Micro-Teaching in Developing Educational Skills According to Some Modern Learning Strategies: An Experimental Study among Female Practical Education Studentsin Faculty of Education Taragen (Sebha University Conference Proceedings, 2025)
The current study aims to identify the effectiveness of microteaching in developing teaching skills according to some modern learning strategies among female practical education students in Faculty of Education Taragen ,In order to achieve the objective of the study and impose the research according to the variable of planning, implementation and evaluation skills  ,an experimental design was used for one experimental group for two pre- and post-measurements to be appropriate with the objectives of the research. The research community consisted of (24) female students in the practical education subject, so that the community itself was selected as a sample for the study due to its number limitations and to make a test for the pre- and post-measurements, consisting of twenty-four items distributed over the three skills, where the pre- and post-test was applied to a survey sample to obtain data related to the validity and reliability of the test, and the results obtained can be presented. The results of the first hypothesis showed that there are differences between the average scores of the pre- and post-test for the experimental group in favor of the post-measurement, and the results of the three sub-hypotheses in the aspect of planning, implementation and evaluation skills showed that there are statistically significant differences between the average scores of the pre- and post-test in favor of the post-measurement, as the most important recommendations of the study are adopting micro-teaching according to modern strategies in preparing practical education students, as well as adopting it within colleges of education for all disciplines in the learning process.